The impact of early Muslim thoughts on the renaissance movement in the west - Abdul Razak, Mohd Abbas; U Tun Aung, Maulana Akbar Shah (2017)
This presentation intends to explain that there was a time in the history of the Muslims known as the ‘Golden Age of Islam’. During that period of time (750-1258), Muslims built their great civilization by merging science and spirituality. They were prepared to learn all that are positive and non-contradictory to their Muslim faith from others; particularly from the Greeks, Persians and Indians. At the peak of their civilization, Europeans came to learn at the Islamic centers for leaning and scientific investigation. In modern times, the West not only failed to acknowledge the contribution of the early Muslim scholars to the Renaissance movement, but also its obsession and passion for science took the masses away from God and spirituality. Looking into the present condition of the world, this presentation calls for an ideal situation that can solve violence, backwardness and moral decadence. It calls upon the West and the Muslim world to share with one another what they have. The West needs spirituality and the Muslim world needs science and technology. It is believed that through such an exchange and sharing between the two, a better world free of violence, hatred and moral decadence can be created.